Identification and Microbial Production of the Raspberry Phenol Salidroside that Is Active against Huntington's Disease. Issue 3 (5th November 2018) - Kallscheuer, Nicolai; Menezes, Regina; Foito, Alexandre; da Silva, Marcelo Henriques; Braga, Adelaide; Dekker, Wijbrand; Sevillano, David Méndez; Rosado-Ramos, Rita; Jardim, Carolina; Oliveira, Joana; Ferreira, Patrícia; Rocha, Isabel; et al.
Abstract : A screen of Rubus idaeus berry fractions for bioactivity against Huntington ' s disease identified salidroside, which was then produced by metabolically engineered microorganisms. Abstract: Edible berries are considered to be among nature's treasure chests as they contain a large number of (poly)phenols with potentially health-promoting properties. However, as berries contain complex (poly)phenol mixtures, it is challenging to associate any interesting pharmacological activity with a single compound. Thus, identification of pharmacologically interesting phenols requires systematic analyses of berry extracts. Here, raspberry ( Rubus idaeus, var Prestige) extracts were systematically analyzed to identify bioactive compounds against pathological processes of neurodegenerative diseases. Berry extracts were tested on different Saccharomyces cerevisiae strains expressing disease proteins associated with Alzheimer's, Parkinson's, or Huntington's disease, or amyotrophic lateral sclerosis. After identifying bioactivity against Huntington's disease, the extract was fractionated and the obtained fractions were tested in the yeast model, which revealed that salidroside, a glycosylated phenol, displayed significant bioactivity. Subsequently, a metabolic route to salidroside was reconstructed in S . cerevisiae and Corynebacterium glutamicum . The best-performing S . cerevisiae strain was capable of producing 2.1 mm (640 mg L −1 ) salidroside from Glc in shake flasks, whereas an engineered C . glutamicum strain could efficiently convert the precursor tyrosol to salidroside, accumulating up to 32 mm (9, 700 mg L −1 ) salidroside in bioreactor cultivations (yield: 0.81 mol mol −1 ). Targeted yeast assays verified that salidroside produced by both organisms has the same positive effects as salidroside of natural origin.